Strengthening Community Empowerment in Developing Seri Elderly Villages for Post-Stroke Patients in the Bandarharjo Semarang Community Health Center Area - Lanny Sunarjo; Rose Asni Latifah; Endah Aryati Ekoningtyas; Sri Widiyati; Lanny Hapsari W (Poltekkes Kemenkes Semarang, 2026)
Stroke is one of the leading causes of long-term disability among older adults and has a significant impact on physical function, nutritional status, oral health, and quality of life. Post-stroke elderly often experience motor impairment, dysphagia, malnutrition, and poor oral hygiene, resulting in increased dependency and decreased well-being. This community service program aimed to strengthen community empowerment through the development of SERI Elderly Villages (Healthy and Independent) for post-stroke patients in the working area of Bandarharjo Community Health Center, Semarang. The program applied a research-based community empowerment approach involving health education, basic health screening, oral hygiene examination, dental scaling, nutrition counseling, physical fitness training, and oral exercise assistance. The targets were post-stroke elderly and their family caregivers in Bandarharjo sub-districts. The results showed improved knowledge, awareness, and independence of post-stroke elderly in performing physical fitness exercises and oral exercises, as well as better self-care and oral hygiene practices. This program supports primary health care transformation through sustainable community empowerment toward healthy and independent elderly communities.